WOMEN'S EMPOWERMENT STRATEGIES IN IMPROVING CHILD PROTECTION IN THE MODERN ERA - Sony Garneta, Belva Fitriyah; Auliyah, Rosyidatul (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
Currently, technological developments are developing rapidly. The advancement of information and communication technology must be balanced with the empowerment of women in improving child protection in the modern era. In this context, women have an important role in protecting children's rights, especially amidst the challenges that arise due to the use of gadgets and social media. This study uses a qualitative method with a document review approach. The purpose of this study is to explore women's empowerment strategies. The results of the study indicate that women's empowerment through education and skills training can improve welfare and independence which contributes to child protection. In addition, this study identifies various risks faced by children in the digital era, such as child abduction, bullying and access to inappropriate content. Therefore, collaboration between parents, society and government is needed to create a safe and supportive environment for children. Women's empowerment and child protection are strategic issues that must be considered to ensure a better future for future generations.